PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENGEMBANGKAN KEPEDULIAN SOSIAL DAN LINGKUNGAN HIDUP SISWA - Parwono Parwono; Pargito Pargito; Darsono Darsono (Faculty of Teacher Training and Education, University of Lampung, 2013)
This study was conducted to improve the learning activity of students in social studies with PBL models and to develop social and environmental concerns with the application of PBL models through learning social studies. The approach used in this study is classroom action research. The results of this study were (1) the application of the Problem Based Learning can enhance the learning activity of students in social studies are realized by working to divide the work in groups to complete a given task teacher, responsible, respectful student opinions and responses during the discussion, and can produce work that can be presented to good, and (2) the application of the problem based learning can improve the social and environmental concerns that have been applied in everyday life evidenced by students while maintaining the cleanliness of the classroom and the surrounding environment by removing waste in place and classrooms neat, clean and terjalinya student interaction is very good. Teachers always instilled in ways that can provide good in social life and environmental and students can receive a fine and can applications in real life everyday in the school environment. Latar Belakang penelitian ini adalah rendahnya aktivitas belajar siswa dan rendahnya kepedulian sosial dan lingkungan hidup. Metode Penelitian ini menggunakan Metode Penelitian Tindakan Kelas. Hasil penelitian menunjukkan bahwa penerapan model Problem Based Learning dapat: (1) Meningkatan aktivitas siswa dalam mengajukan pertanyaan, menjawab/menanggapi pertanyaan, menulis/mencatat, membaca, mendengarkan/ memperhatikan guru, bekerja dalam kelompok belajar, menggali informasi, mengambil keputusan dalam pemecahan masalah, kerjasama dalam kelompok, menghargai pendapat orang lain dan menerima penghargaan. (2) Meningkatan kemampuan siswa dalam mengembangkan kepedulian sosial dan lingkungan hidup, yang dapat dilihat dari penerapan kehidupan sehari-hari dengan kebiasaan menjaga lingkungan hidup dan kepedulian sosial.Kata kunci: problem based learning, kepedulian sosial, lingkungan hidup